Essential magnetosome proteins MamI and MamL from magnetotactic bacteria interact in mammalian cells - Qin Sun; Liu Yu; Sarah C. Donnelly; Cécile Fradin; R. Terry Thompson; Frank S. Prato; Donna E. Goldhawk (Scientific Reports, 2024)
Abstract To detect cellular activities deep within the body using magnetic resonance platforms, magnetosomes are the ideal model of genetically-encoded nanoparticles. These membrane-bound iron biominerals produced by magnetotactic bacteria are highly regulated by approximately 30 genes; however, the number of magnetosome genes that are essential and/or constitute the root structure upon which biominerals form is largely undefined. To examine the possibility that key magnetosome genes may interact in a foreign environment, we expressed mamI and mamL as fluorescent fusion proteins in mammalian cells. Localization and potential protein-protein interaction(s) were investigated using confocal microscopy and fluorescence correlation spectroscopy (FCS). Enhanced green fluorescent protein (EGFP)-MamI and the red fluorescent Tomato-MamL displayed distinct intracellular localization, with net-like and punctate fluorescence, respectively. Remarkably, co-expression revealed co-localization of both fluorescent fusion proteins in the same punctate pattern. An interaction between MamI and MamL was confirmed by co-immunoprecipitation. In addition, changes in EGFP-MamI distribution were accompanied by acquisition of intracellular mobility which all Tomato-MamL structures displayed. Analysis of extracts from these cells by FCS was consistent with an interaction between fluorescent fusion proteins, including an increase in particle radius. Co-localization and interaction of MamI and MamL demonstrate that select magnetosome proteins may associate in mammalian cells.